(untitled) (Global Journal of Human-Social Science, 2014)
Early in the twentieth centurysome frivolous types of works in its staging began to appear in the Spanish lyric theaters showing curves and calves of the treble singers. Couplets and other musical numbers conferred a racy and risqué tone that was all the rage, especially among the male audience. Authorities and the church attacked this kind of theater. Morality in the theater had changed.